The effects of human capital on wages, and the determinants of labor supply in a developing country - Sahn, David E.; Alderman, Harold (Elsevier, 1988)
The Heckman procedure is used to correct for sample selection bias in estimating wage offer and net labor market supply equations. The findings show that wages are affected by education and experience. In addition, the wage offer is influenced by other genetic and environmental influences captured in the wage of one's father. Calories, as predicted by exogenous instruments, are also shown to influence the wage offer, suggesting that better nutrition increases labor productivity. The probability of market labor participation as well as the amount of net market labor supply declined with the size of paddy landholding, in addition to the net market supply elasticity increasing with the amount of land owned, and being lower for urban than rural workers.